Proline-mediated regulation on jasmonate signals repressed anthocyanin accumulation through the MYB-bHLH-WDR complex in rice under chromium exposure - Zhang, Qing; Feng, Yu-Xi; Tian, Peng; Lin, Yu-Juan; Yu, Xiao-Zhang (Frontiers in Plant Science, 2022)
Toxic metal-induced accumulation of anthocyanin (ATH) in plants can oxidize proteins and break DNA. Herein, the role of exogenous proline (Pro) on repression of ATH accumulation in rice seedlings during hexavalent chromium [Cr(VI)] exposure was studied. Results indicated that exogenous Pro-mediated regulation of jasmonate signals activated the MYB-bHLH-WDR complex to repress ATH accumulation in rice tissues under Cr(VI) stress. Biochemical and transcript analysis indicated that exogenous Pro promoted the synthesis of jasmonic acid (JA) and its molecularly active metabolite jasmonic acid isoleucine (JA-Ile) in rice tissues under Cr(VI) stress. Increment in the endogenous level of jasmonates positively triggered the expression of genes responsible for the JA signaling pathway and activated the MYB-bHLH-WDR complex, eventually repressing the glycosylation of anthocyanidin to form ATH in rice tissues. In conclusions, exogenous Pro-mediated regulation on jasmonate signals was tissue-specific under Cr(VI) stress, and more positive effect was detected in shoots rather than roots.